Stroke cycle (Rowing Biomechanics Newsletter, 2013)
The purpose of this article is twofold: 1) to describe our model of rowing technique; 2) to clarify definitions of rowing biomechanics terminology. The stroke cycle is presented as 8 "Moments" M1-M8-momentary snapshots, and 8 "Phases" P1-P8 -transitions between the moments. The main biomechanical variables during the stroke cycle are presented in table 1.